Neck Posture Clusters and Their Association With Biopsychosocial Factors and Neck Pain in Australian Adolescents. Issue 10 (1st October 2016) - Richards, Karen V.; Beales, Darren J.; Smith, Anne J.; O'Sullivan, Peter B.; Straker, Leon M.
Abstract: Background: There is conflicting evidence on the association between sagittal neck posture and neck pain. Objective: The purposes of this study were: (1) to determine the existence of clusters of neck posture in a cohort of 17-year-olds and (2) to establish whether identified subgroups were associated with biopsychosocial factors and neck pain. Design: This was a cross-sectional study. Methods: The adolescents (N=1, 108) underwent 2-dimensional photographic postural assessment in a sitting position. One distance and 4 angular measurements of the head, neck, and thorax were calculated from photo-reflective markers placed on bony landmarks. Subgroups of sagittal sitting neck posture were determined by cluster analysis. Height and weight were measured, and lifestyle and psychological factors, neck pain, and headache were assessed by questionnaire. The associations among posture subgroups, neck pain, and other factors were evaluated using logistic regression. Results: Four distinct clusters of sitting neck posture were identified: upright, intermediate, slumped thorax/forward head, and erect thorax/forward head. Significant associations between cluster and sex, weight, and height were found. Participants classified as having slumped thorax/forward head posture were at higher odds of mild, moderate, or severe depression. Participants classified as having upright posture exercised more frequently. There was no significant difference in the odds of neck pain or headache across the clusters. Limitations: The results are specific to 17-year-olds and may not be applicable to adults. Conclusion: Meaningful sagittal sitting neck posture clusters were identified in 17-year-olds who demonstrated some differences with biopsychosocial profiling. The finding of no association between cluster membership and neck pain and headaches challenges widely held beliefs about the role of posture in adolescent neck pain.